A Dynamic Analysis of the Multi-Stack SOFC-CHP System for Power Modulation - Cheng-Hao Yang; Shing-Cheng Chang; Yen-Hsin Chan; Wen-Sheng Chang (Energies, 2019)
This paper performs a dynamic analysis of a 10-kW solid oxide fuel cell/combined heat and power (SOFC-CHP) system with a multi-stack module via numerical simulations. The performance of stacks, tail gas burners, heat exchangers, and fuel reformers are modeled by the MATLAB/Simulink module. The effects of fuel and air maldistribution on SOFC-CHP systems are addressed in this work. A two-stack module for 10-kW power generation is adopted to represent the multi-stack module with high power modulation. The air flow rate and operating current, which are related to the fuel use rate of an SOFC system, should be optimally regulated to perform with maximum power generation and efficiency. The proposed dynamic analysis shows that the operating temperatures of the two stacks have a difference of 33 K, which results in a reduced total power generation of 9.77 kW, with inconsistent fuel use (FU) rates of 78.3% and 56.8% for the two stacks. With the optimal control strategy, the output power is increased to 10.6 kW, an increment of 8.5%, and the FU rates of the two stacks are improved to 79% and 70%, respectively. As a potential distributed power generator, the long-term effects of the studied SOFC-CHP systems are also investigated. The dynamic analysis of the long-term operating SOFC-CHP system shows that the total daily output power can be increased 7.34% by using the optimal control strategy.